Firm heterogeneity and the impact of payroll taxes - Anikó Bíró; Attila Lindner; Daniel Prinz; Réka Branyiczki; Lili Márk (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
We study the impact of a large payroll tax cut for older workers in Hungary. Motivated by the predictions of a standard equilibrium job search model, we examine the heterogeneous impact of the policy. Employment increases most at low-productivity firms offering low-wage jobs, which tend to hire from unemployment, while the effects are more muted for highproductivity firms offering high-wage jobs. At the same time, wages only increase at highproductivity firms. These results point to important heterogeneity in the incidence of payroll tax cuts across firms and highlight that payroll taxes have a significant impact on the composition of jobs in the labor market.
Keywords: H24; H32; J23; J31; 330; payroll tax; tax incidence; firm heterogeneity